Childhood tuberous sclerosis complex in southern Sweden: a paradigm shift in diagnosis and treatment - Pearsson, Kevin; Björk Werner, Josefin; Lundgren, Johan; Gränse, Lotta; Karlsson, Emma; Källén, Kristina; Eklund, Erik A.; Bekassy, Zivile (BMC pediatrics, 2023)
To investigate the complete clinical spectrum of individuals with paediatric tuberous sclerosis complex in southern Sweden and explore changes over time. In this retrospective observational study, 52 individuals aged up to 18 years at the study start were followed-up at regional hospitals and centres for habilitation from 2000 to 2020. Cardiac rhabdomyoma was detected prenatally/neonatally in 69.2% of the subjects born during the latest ten years of the study period. Epilepsy was diagnosed in 82.7% of subjects, and 10 (19%) were treated with everolimus, mainly (80%) for a neurological indication. Renal cysts were detected in 53%, angiomyolipomas in 47%, astrocytic hamartomas in 28% of the individuals. There was a paucity of standardized follow-up of cardiac, renal, and ophthalmological manifestations and no structured transition to adult care. Our in-depth analysis shows a clear shift towards an earlier diagnosis of tuberous sclerosis complex in the latter part of the study period, where more than 60% of cases showed evidence of this condition already in utero due to the presence of a cardiac rhabdomyoma. This allows for preventive treatment of epilepsy with vigabatrin and early intervention with everolimus for potential mitigation of other symptoms of tuberous sclerosis complex.